The Determinants of Purchase Intention Halal Products: The Moderating Role of Religiosity - Nora, Liza; Sriminarti, Nurul (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Halal marketing is an important concept for marketers doing business in Muslim-majority countries. To predict consumer behavior toward halal products, the Theory of Reasoned Action (TRA) explains the two components of the formation of purchase intentions, namely attitude and subjective norms. Consumer concern for the lawfulness of a product is also influenced by a person's level of religiosity. This study aims to empirically test the ability of religiosity as a moderator that affects attitudes, and subjective norms on purchase intentions. This study applied a quantitative design. One hundred and ninety respondents in Indonesia were collected through random sampling. Data were collected through an online questionnaire using Google Forms and analyzed by Structural Equation Modelling (SEM). This study explains that subjective attitudes and norms have a positive and significant effect on purchase intentions. Religiosity as a moderator is able to influence subjective attitudes and norms on purchase intentions. The results of this study provide information that halal products are unique because they have spiritual elements. In this regard, marketers must remember that Muslim consumers exercise additional vigilance to ensure that the product fulfills not only functional needs but also spiritual needs.